Navigating War Zones: Safeguarding Civilian Rights to Life and Religion through International and Islamic Law - Ashraf, Samina; Nazir, Mahwish (International Journal of Education, Culture, and Society, 2023)
This study explores the protection of civilian rights, focusing on the right to life and religious freedom, within Islamic and international legal contexts. It comprises two main aspects: "The entitlement to life and the prohibition of torture and inhuman treatment" and "Right to respect for religious beliefs, customs, and traditions. In a post-9/11 world, where misconceptions about jihad have proliferated, this research distinguishes between Islamic legal theory and the legislation of Muslim nations. It argues that Islamic law has historically played a pivotal role in safeguarding civilian rights during armed conflicts. It predates the Declaration of Human Rights on a global scale by centuries and aligns with modern international conventions. Islamic humanitarian law reveres civilian rights, condemning violations as crimes against humanity. Through rigorous research, including a review of primary sources in Islamic and international law, this study sheds light on the historical evolution and contemporary relevance of these legal frameworks. It highlights the enduring significance of principles rooted in Islamic law, in harmony with modern international human rights standards. In conclusion, this research provides an in-depth exploration of the intersection of Islamic and international law in safeguarding civilian rights during conflicts. Understanding these legal frameworks in their historical context is essential for global peace and justice.